Accessory Atrioventricular Pathways Refractory to Catheter Ablation. (February 2015) - Scanavacca, Maurício Ibrahim; Sternick, Eduardo Back; Pisani, Cristiano; Lara, Sissy; Hardy, Carina; d'Ávila, André; Correa, Frederico Soares; Darrieux, Francisco; Hachul, Denise; Marcial, Miguel Barbero; Sosa, Eduardo A.
<x xml:space="preserve">Abstract</x> Background— Epicardial mapping and ablation of accessory pathways through a subxiphoid approach can be an alternative when endocardial or epicardial transvenous mapping has failed. Methods and Results— We reviewed acute and long-term follow-up of 21 patients (14 males) referred for percutaneous epicardial accessory pathway ablation. There was a median of 2 previous failed procedures. All patients were highly symptomatic, 8 had atrial fibrillation (3 with cardiac arrest) and 13 had frequent symptomatic episodes of atrioventricular reentrant tachycardia. Six patients (28.5%) had a successful epicardial ablation. Five patients (23.8%) underwent a successful repeated endocardial mapping, and ablation after epicardial mapping yielded no early activation site. Epicardial mapping was helpful in guiding endocardial ablation in 2 patients (9.5%), showing that the earliest activation was simultaneous at the epicardium and endocardium. Four patients (19%) underwent successful open-chest surgery after failing epicardial/endocardial ablation. Two patients (9.5%) remained controlled under antiarrhythmic drugs after unsuccessful endocardial/epicardial ablation. Two patients had a coronary sinus diverticulum and one a right atrium to right ventricle diverticulum. Three patients acquired postablation coronary sinus stenosis. There was no major complication related to pericardial access. Conclusions— Percutaneous epicardial approach is an alternative when conventional endocardial or transvenous epicardial ablation fails in the elimination of the accessory pathway. A new attempt by endocardial approach was successful in a significant number of patients. Open-chest surgery may be required in symptomatic cases refractory to endocardial–epicardial approach.